Long-Term Outcomes Following Drug-Eluting Balloons Versus Thin-Strut Drug-Eluting Stents for Treatment of In-Stent Restenosis (DEB-Dragon-Registry). (3rd September 2021) - Wańha, Wojciech; Bil, Jacek; Januszek, Rafał; Gilis-Malinowska, Natasza; Figatowski, Tomasz; Milewski, Marek; Pawlik, Artur; Staszczak, Bartłomiej; Wybraniec, Maciej; Tomasiewicz, Brunon; Kübler, Piotr; Kuliczkowski, Wiktor; et al.
Abstract : Supplemental Digital Content is available in the text. Abstract : Background: Data regarding the use of percutaneous coronary intervention with drug-eluting balloons (DEB) versus thin-strut drug-eluting stents (thin-DES) for treating DES in-stent restenosis in everyday clinical practice is scarce. Our goal was to evaluate the efficacy and safety profile of DEB versus thin-DES in DES in-stent restenosis. Methods: Consecutive patients with DES in-stent restenosis who underwent percutaneous coronary intervention between 2008 and 2019 entered the multicenter DEB-DRAGON Registry with a follow-up of 3 years. Patients who received DEB at the index procedure (n=557, 49.9%) were compared with those who received thin-DES (n=560, 50.1%). Results: Analysis of the unmatched cohort revealed lower rates of target lesion revascularization (9.1% versus 13.6%; hazard ratio [HR], 0.58 [95% CI, 0.41–0.83], P =0.003), target vessel revascularization (11.8% versus 16.7%; HR, 0.62 [95% CI, 0.45–0.84], P =0.003) and device-oriented composite end point, defined as a composite of cardiac death, target lesion revascularization, and target vessel myocardial infarction (12.7% versus 16.0%; HR, 0.69 [95% CI, 0.50–0.94], P =0.018) in the thin-DES group compared with the DEB group. The incidence of cardiac death, target vessel-myocardial infarction, and myocardial infarction were similar in both groups. However, after propensity score matching, there were no significant differences in target lesion revascularization (11.2% versus 11.2%; HR, 0.91 [95% CI, 0.55–1.51], P =0.707), target vessel revascularization (13.4% versus 14.2%; HR, 0.86 [95% CI, 0.55–1.36], P =0.523), and device-oriented composite end point (14.2% versus 14.2%; HR, 0.91 [95% CI, 0.58–1.42], P =0.667) between the thin-DES and DEB group, respectively. Conclusions: This analysis of a real-life registry revealed similar long-term outcomes of thin-DES and DEB in DES in-stent restenosis regarding target lesion revascularization, myocardial infarction, cardiac death, and device-oriented composite end point. Registration: URL: https://www.clinicaltrials.gov ; Unique identifier: NCT04415216.